Encyclopedia of American Activism : 1960 to the Present. - DiCanio, Margaret (Open Road Distribution, 2016)
The turbulence of the 1960s and 1970s spawned a spectrum of activist movements. In spirit and action, events ranged from: gentle to violent; from Tree People to Bloody Sunday; from Community Mental Health to Black Power. This rapid stream of social and political change defined the second half of the 20th century, yet had roots in the first half. The baby boom generation launched many movements. Unlike their Depression/WWII parents, the boomers, a large cohort of unattached, young adults, had no looming familial and social responsibilities. They had the freedom and resources for the consuming task of changing the world.